Cultural epigenetics. Issue 1 (March 2016) - Jablonka, Eva
Abstract: Taking a Waddingtonian system approach, I discuss some of the implications of recent epigenetic research for the study of social systems. A growing number of investigations show that life‐style changes resulting from nutritional, toxicological, and psychological stresses are reflected in changes in the epigenetic profile of individuals, and that learning and memory have epigenetic correlates. Moreover, various types of epigenetic changes can be inherited and affect the characters of descendants. Studying epigenetics can forge new experimental and conceptual bridges between biology, the social sciences and the humanities. For example, new techniques that allow the deciphering of methylation patterns in ancient DNA could be used to study the epigenetics of human cultures in long‐gone historical periods, thus enriching and extending our knowledge of human history. Conceptually, an epigenetic perspective blurs traditional distinctions such as those between nature and nurture, plasticity and evolvability.